Consumption and Economic Life in Modern Latin America - Otero-Cleves, Ana María (History compass, 2025)
Commodities and global trade are central to the history of Latin America. As scholars have pointed out, the cultivation, extraction, and shipping of commodities produced in the Americas have been vital in deepening our knowledge of the scale of its global entanglements. While crucial for understanding the region's political, economic and cultural past, this approach has inadvertently overlooked the equally vital role of consumption. This article aims to cast light on how the studies on the history of consumption—histories of what people bought, owned, ate, wore, and discarded—can provide greater insight into the region's cultural, political, and economic history from the 1820s until the mid-20th century. It prioritizes scholarship that recognizes Latin American consumers as active agents of historical change. The article also aims to show how the history of consumption can bridge various historiographical fields—including environmental history, the history of capitalism, labor history, and the history of race—to offer a richer and more comprehensive knowledge of Latin America's past.